Correlation of Histopathological Findings in Laryngeal Squamous Cell Carcinoma with Inflammatory Biomarkers - OYSU, ÇAĞATAY (DEOMED PUBL, ISTANBUL, 2019)
Objective: The goal of this research was to investigate how biomarkers, i.e. SII (an index calculated from blood counts of various leucocytes), NLR and MLR correlate with features used in the staging of laryngeal squamous cell carcinoma (LSCC), i.e. perineural infiltration, lymphatic involvement and histological grade. Methods: A retrospective review of clinical records from 146 cases (143 men and 3 women) of LSCC occurring between January 2008 and January 2018 was undertaken. The sample included every stage of LSCC and all biomarker results were found from the full blood count (FBC) results obtained prior to surgery and documented for each case. SII is a newly introduced index of inflammation calculated according to the formula: SII = NxP/L, where N represents neutrophil, P platelet and L lymphocyte counts. Histopathological parameters (presence of perineural or lymphatic involvement, grade of tumour) were evaluated alongside results for NLR, MLR and SII. Results: All three biomarkers were different at the level of statistical significance between individuals with LSCC and the controls. For NLR, p=0.003; for MLR, p=0.008; for SII, p<0.001. Both NLR and SII were different at a statistically significant level when compared at early and advanced stages of LSCC (p values were 0.011 and <0.001, respectively. MLR did not differ at the level of statistical significance (p=0.944). (See Table 3). Conclusion: SII is straightforward to calculate, economical and reproducible from FBC results. It can provide important clues to the likelihood of perineural or lymphatic involvement in cases of LSCC.
Keywords: Laryngeal squamous cell carcinoma; inflammatory biomarkers; systemic immune-inflammation index; TO-LYMPHOCYTE RATIO; CURATIVE RESECTION; PROGNOSTIC-FACTOR; CANCER; NEUTROPHIL; SURVIVAL; COUNTS; TUMORS; INDEX